Doctoral study and getting published : narratives of early career researchers - Fay, Richard; Kostoulas, Achilleas (Surviving and thriving in academia, 2025)
Pressure to share research findings in the form of academic publications has meant that doctoral candidates are encouraged to develop skills that will help them engage with the competitive publication market. Doctoral Study and Getting Published features a collection of early career research narratives that focuses on researcher development and education. There is an emphasis on the often pressurised process of publishing during or after a doctorate through an ecological perspective. The book brings together a diverse but coherent set of voices, reflections and advice from early-career researchers regarding publication experiences. Issues explored include academic identity, collaboration (including include student-supervisor relationships, co-authorship and working in research groups), dynamics of larger scholarly communities and engaging with publishers and reviewer feedback. The book is intended as a supplementary resource for use by doctoral students and early career researchers in the Humanities and Social Sciences, whether they are enrolled in academic writing programmes or working individually to develop their authorial identity.